A swift approach for identifying vulnerable linear transport infrastructures in areas prone to floods and erosion - Arras, Claudio; Calia, Mara; Da Pelo, Stefania; Coni, Mauro; Maltinti, Francesca (Italian journal of engineering geology and environment, 2024)
Linear transport infrastructures are essential for the socioeconomic development of industrialized countries. However, adverse meteorological and hydrogeological events can result in significant economic losses. Globally, floods have the most substantial socio-economic impact. Climate Change, due to the extent of transport infrastructures over flood-prone territories, is a very important factor in worsening flood risk. The main objective of this study is to identify the sections of the hydrographic network that are susceptible to flood and erosion hazards where road infrastructures are located. The Metropolitan City of Cagliari (Sardinia, Italy) is selected as test site, due to the presence of several coastal watersheds and of a high population density. A swift methodological approach, based on already available datasets from public repositories and GIS analyses, is presented. This approach includes: i) geomorphological characterization of the hydrographic network; ii) census of stream tracts where bridges were damaged in past flood events; iii) identification of potentially critical tracts (PCT), based on similar geomorphological conditions; iv) multi-temporal satellite imagery analysis of PCT for the identification of flood-prone areas and, therefore, vulnerable road crossings. The adopted methodology has proved to be effective for the identification of vulnerable road crossings over wide portion of territories, identifying critical sites that need further investigation.